“I Came Not to Abolish”: Contextualizing the Christian Relationship to the Law through Jewish Understanding of Torah - Passinault, Noah (Lumen et Vita, 2024)
In the context of spirituality, the Christian view of law is usually a negative one seen in relation to grace. Law is rigid and stifling; grace is free and liberating. Only a surface level reading of the Bible, however, reveals a positive view of law that pervades the language and identity of Scripture in spite of this common perception. In order to show that the attitude of Christian spirituality towards law should not be one of rejection but one of incorporation, I will begin with an examination of the Jewish understanding of torah as a way of life based on the imitation of God’s love. This concept of torah as primarily describing a way of life rather than a series of rules will then be applied to Jesus’ statement in Matthew 5:17 that he “has come not to abolish [the law] but to fulfill”. This will be done in order to explore further how Christians are called to integrate the contemplative and practical aspects of their faith through interpretation of the written word. In summary, an understanding of torah as describing a life of interpreting the relationship between contemplation and practice both more closely adheres to the understanding of torah as used by Jesus himself and is more useful when determining a practical approach to Christian spirituality regarding the law. This will be accomplished by looking primarily at Jewish scholars of the Hebrew Bible, as well as both Jewish and Christian interpretations of the New Testament. This examination is not an appropriation of Jewish identity or practice, but a recognition that any understanding of the message of Scripture for any audience (Christian,Jewish, or other) should begin by referring to the context in which it was written; in this case, the Jewish context of the gospel authors.